Answer:
The point after the reflection of (-4,-3) across the y-axis is:
Hence, option B is correct.
Explanation:
When a point P(x, y) is reflected across the y-axis, we reverse the sign of the x-coordinate while the y-coordinate remains the same.
Thus,
The rule to reflect a point across the y-axis is:
P(x, y) → P'(-x, y)
In our case, we are given the point (-4, -3)
Let say the point is A(-4, -3)
Thus, using the rule to reflect a point across the y-axis is:
P(x, y) → P'(-x, y)
A(-4, -3) → A'(-(-4), -3) → A'(4, -3)
Therefore, the point after the reflection of (-4,-3) across the y-axis is:
Hence, option B is correct.